Tourism and Hotels in Sarawak: Economic Performance - Dayang Hummida, Abang Abdul Rahman; Dayang Affizzah, Awang Marikan; Salbiah, Edman (Elsevier Ltd., 2012)
This study investigates the relationship between output growth in the hotels industry in Sarawak (in term of Revenue),tourist arrivals, exchange rate and economic growth in Sarawak, using the time series data from 1975 to 2004. An Augmented-Dickey Fuller (ADF) unit root test, Johansen and Juselius cointegration approach and causality test based on Vector Error Correction Model (VECM) were deployed to run the analysis. The findings show the existent of the long-run and short-run relationship between the variables. Besides that, the results reveal that tourist arrivals have apositive impact on growth. However exchange rate has a negative impact on economic growth.